State Budget Periodicity and General Expenditure Volatility: An Empirical Analysis - Kim, Soojin (2017)
This article aims to examine empirically the relationship between budget periodicity and expenditure volatility in state governments. Using a large panel dataset for fifty states over the years 1960–2012, after controlling for institutional, economic, and political factors, we find general expenditure of biennial states has been significantly less volatile than that of annual states. The finding suggests that a choice between annual and biennial budget period can emerge as a feasible and effective countercyclical strategy to overcome fiscal difficulties in the short run and promote fiscal stability in the long run.